Flowability improver for resin composition, molded body and low dielectric resin

JP7643389B2Active Publication Date: 2025-03-11ARAKAWA CHEM IND LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022070544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-04-22
Publication Date
2025-03-11
Estimated Expiration
2042-04-22

AI Technical Summary

Benefits of technology

【0018】 本発明の樹脂組成物は、液晶ポリマー、ポリフェニレンエーテル樹脂、ポリフェニレンサルファイド樹脂及びポリブチレンテレフタレート樹脂等の低誘電性樹脂が有する低誘電特性を維持しつつ、その成形加工性に優れる。また、本発明の樹脂組成物は、成形時における発煙が抑制されている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643389000001
    Figure 0007643389000001
  • Figure 0007643389000002
    Figure 0007643389000002
  • Figure 0007643389000003
    Figure 0007643389000003
Patent Text Reader

Abstract

To provide a low-dielectric resin composition that retains low dielectric properties of low-dielectric resins such as liquid crystal polymer, polyphenylene ether resin, polyphenylene sulfide resin and polybutylene terephthalate resin, while having reduced smoking during molding, and offering sufficient moldability.SOLUTION: A resin composition contains at least one resin selected from the group consisting of liquid crystal polymer, polyphenylene ether resin, polyphenylene sulfide resin and polybutylene terephthalate resin (A), and petroleum resin (B). The petroleum resin (B) has a 5% weight loss temperature of 270°C or higher. The petroleum resin (B) has a mixed methylcyclohexaneaniline cloud point (MMAP) of 10-95°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a molded article, and a flowability improver for a low dielectric resin. [Background technology]

[0002] In recent years, there has been a demand for high-speed transmission and reception of large volumes of data in communication devices such as smartphones and electronic devices such as next-generation televisions. Accordingly, the frequencies of electrical signals are becoming higher. Specifically, in the field of wireless communication, high-frequency bands of 10 GHz or higher are being used with the introduction of the fifth generation mobile communication system (5G).

[0003] However, as the frequency of the signal used increases, the quality of the output signal decreases, which can lead to erroneous recognition of information, i.e., the transmission loss increases. This transmission loss is made up of conductor loss caused by the conductor and dielectric loss caused by the insulating resin that constitutes the electrical and electronic components such as boards in electronic devices and communication devices. Since conductor loss is proportional to the 0.5th power of the frequency used and dielectric loss is proportional to the 1st power of the frequency, the impact of this dielectric loss becomes extremely large in high frequency bands, especially in the GHz band.

[0004] In order to reduce this transmission loss, there is a demand for low dielectric resins that have low relative permittivity and dielectric loss tangent, which are factors related to dielectric loss (hereinafter also referred to as low dielectric properties). For example, liquid crystal polymers, polyphenylene ether resins, polyphenylene sulfide resins, polybutylene terephthalate resins, etc. have been considered as such low dielectric resins (Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-250620 A [Patent Document 2] JP 2019-131685 A [Patent Document 3] JP 2014-198778 A [Patent Document 4] JP 2013-043942 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, low dielectric resins such as liquid crystal polymers, polyphenylene ether resins, polyphenylene sulfide resins, and polybutylene terephthalate resins have a high glass transition temperature, a high melting point, and a high melt viscosity, and therefore have poor moldability. In addition, when a conventional flow improver is used with these low dielectric resins to improve moldability, the low dielectric properties of the low dielectric resins may be reduced, and the low dielectric properties may not be suitable for electronic materials used in high frequency regions (GHz bands). Furthermore, the molding temperature of these low dielectric resins is very high, at 250°C or higher, and there is also a problem of smoke generation when molding with the addition of a conventional flow improver.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a resin composition that maintains the low dielectric properties of low dielectric resins such as liquid crystal polymers, polyphenylene ether resins, polyphenylene sulfide resins, and polybutylene terephthalate resins, while suppressing smoke generation during molding and exhibiting excellent moldability.

[0008] Another object of the present invention is to provide a novel flowability improver that can suppress smoke generation during molding of a low dielectric resin while maintaining the low dielectric properties of the low dielectric resin, and can improve the molding processability of the low dielectric resin. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a composition using a specific petroleum resin as the low dielectric resin. The present inventors have also found that the above-mentioned problems can be solved by a flow improver containing a specific petroleum resin. That is, the present invention relates to the following resin composition, molded product, and flow improver.

[0010] 1. A composition comprising at least one resin (A) selected from the group consisting of a liquid crystal polymer, a polyphenylene ether resin, a polyphenylene sulfide resin, and a polybutylene terephthalate resin, and a petroleum resin (B); The petroleum resin (B) has a 5% weight loss temperature of 270° C. or higher, The resin composition, wherein the petroleum resin (B) has a mixed methylcyclohexaneaniline cloud point (MMAP) of 10 to 95°C.

[0011] 2. The resin composition according to item 1, wherein the liquid crystal polymer is a liquid crystal polyester.

[0012] 3. The resin composition according to item 1 or 2, wherein the softening point of component (B) is 120 to 190°C.

[0013] 4. The resin composition according to any one of items 1 to 3, wherein the content of the component (B) is 0.1 to 10 parts by mass per 100 parts by mass of the component (A).

[0014] 5. A molded article obtained from the resin composition according to any one of items 1 to 4 above.

[0015] 6.5% weight loss temperature is 270°C or higher; A flow improver for low dielectric resins, comprising a petroleum resin (B) having a mixed methylcyclohexaneaniline cloud point (MMAP) of 10 to 95°C.

[0016] 7. The flow improver for low dielectric resin according to item 6, wherein the softening point of component (B) is 120 to 190°C.

[0017] 8. The fluidity improver for a low dielectric resin according to item 6 or 7, wherein the low dielectric resin is at least one resin selected from the group consisting of a liquid crystal polymer, a polyphenylene ether resin, a polyphenylene sulfide resin, and a polybutylene terephthalate resin. Effect of the Invention

[0018] The resin composition of the present invention has excellent moldability while maintaining the low dielectric properties of low dielectric resins such as liquid crystal polymers, polyphenylene ether resins, polyphenylene sulfide resins, and polybutylene terephthalate resins. In addition, the resin composition of the present invention suppresses smoke generation during molding.

[0019] The fluidity improver of the present invention, when used in a low dielectric resin, improves the molding processability of the low dielectric resin while maintaining the low dielectric properties of the low dielectric resin. In addition, the fluidity improver of the present invention can suppress smoke generation during molding of the low dielectric resin. BEST MODE FOR CARRYING OUT THEINVENTION

[0020] [Resin composition] The resin composition of the present invention contains at least one resin (A) (hereinafter also referred to as component (A)) selected from the group consisting of a liquid crystal polymer, a polyphenylene ether resin, a polyphenylene sulfide resin, and a polybutylene terephthalate resin, and a petroleum resin (B) (hereinafter also referred to as component (B)).

[0021] <Resin (A)> The component (A) is not particularly limited as long as it is at least one resin selected from the group consisting of liquid crystal polymers, polyphenylene ether resins, polyphenylene sulfide resins, and polybutylene terephthalate resins, and various known resins can be used. The component (A) may be used alone or in combination of two or more.

[0022] (Liquid Crystal Polymer) The liquid crystal polymer is not particularly limited, and various known liquid crystal polymers can be used. The liquid crystal polymer may be used alone or in combination of two or more kinds.

[0023] Examples of the liquid crystal polymer include liquid crystal polyester and liquid crystal polyester amide. The liquid crystal polyester is not particularly limited, but examples thereof include aromatic polyester, and among them, fully aromatic polyester made using only aromatic compounds as raw material monomers is preferred. The liquid crystal polyester amide is not particularly limited, but examples thereof include aromatic polyester amide, and among them, fully aromatic polyester amide made using only aromatic compounds as raw material monomers is preferred. In addition, polyesters partially containing aromatic polyesters or aromatic polyester amides in the same molecular chain can also be used as the liquid crystal polymer.

[0024] The aromatic polyester is not particularly limited, but may be, for example, (1) Polyesters consisting essentially of one or more aromatic hydroxycarboxylic acids and their derivatives; (2) Mainly (a) one or more aromatic hydroxycarboxylic acids and their derivatives, (b) polyesters composed of one or more of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (3) Mainly (a) one or more aromatic hydroxycarboxylic acids and their derivatives, (b) one or more of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (c) Polyesters composed of one or more of aromatic diols, alicyclic diols, aliphatic diols, and derivatives thereof.

[0025] The aromatic polyester amide is not particularly limited, but may be, for example, (1) Mainly (a) one or more aromatic hydroxycarboxylic acids and their derivatives, (b) one or more of aromatic hydroxyamines, aromatic diamines, and derivatives thereof; (c) polyesteramides composed of one or more of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (2) Mainly (a) one or more aromatic hydroxycarboxylic acids and their derivatives, (b) one or more of aromatic hydroxyamines, aromatic diamines, and derivatives thereof; (c) one or more of aromatic dicarboxylic acids, alicyclic dicarboxylic acids, and derivatives thereof; (d) polyesteramides composed of one or more of aromatic diols, alicyclic diols, aliphatic diols, and derivatives thereof. Furthermore, a molecular weight modifier may be used in combination with the above-mentioned components, if necessary.

[0026] Examples of the aromatic hydroxycarboxylic acid include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and 6-hydroxy-1-naphthoic acid, and 3-methyl-4-hydroxybenzoic acid, 3,5-dimethyl-4-hydroxybenzoic acid, 2,6-dimethyl-4-hydroxybenzoic acid, 3-methoxy-4-hydroxybenzoic acid, 3,5-dimethoxy-4-hydroxybenzoic acid, 6-hydroxy-5-methyl-2-naphthoic acid, and 6-hydroxy-5-methoxy-2-naphthoic acid. Examples of aromatic hydroxycarboxylic acids include alkyl, alkoxy, or halogen-substituted derivatives of naphthoic acid, 2-chloro-4-hydroxybenzoic acid, 3-chloro-4-hydroxybenzoic acid, 2,3-dichloro-4-hydroxybenzoic acid, 3,5-dichloro-4-hydroxybenzoic acid, 2,5-dichloro-4-hydroxybenzoic acid, 3-bromo-4-hydroxybenzoic acid, 6-hydroxy-5-chloro-2-naphthoic acid, 6-hydroxy-7-chloro-2-naphthoic acid, and 6-hydroxy-5,7-dichloro-2-naphthoic acid.

[0027] Examples of the aromatic diol include aromatic diols such as 4,4'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxyterphenyl, hydroquinone, resorcin, 2,6-naphthalenediol, 4,4'-dihydroxydiphenyl ether, bis(4-hydroxyphenoxy)ethane, 3,3'-dihydroxydiphenyl ether, 1,6-naphthalenediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)methane; and alkyl, alkoxy, or halogen-substituted aromatic diols such as chlorohydroquinone, methylhydroquinone, tert-butylhydroquinone, phenylhydroquinone, methoxyhydroquinone, phenoxyhydroquinone, 4-chlororesorcin, and 4-methylresorcin.

[0028] Examples of the aromatic dicarboxylic acid include aromatic dicarboxylic acids such as terephthalic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-triphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenoxybutane-4,4'-dicarboxylic acid, diphenylethane-4,4'-dicarboxylic acid, isophthalic acid, diphenylether-3,3'-dicarboxylic acid, diphenoxyethane-3,3'-dicarboxylic acid, diphenylethane-3,3'-dicarboxylic acid, and 1,6-naphthalenedicarboxylic acid, and alkyl, alkoxy, or halogen-substituted derivatives of the aromatic dicarboxylic acids represented by chloroterephthalic acid, dichloroterephthalic acid, bromoterephthalic acid, methylterephthalic acid, dimethylterephthalic acid, ethylterephthalic acid, methoxyterephthalic acid, and ethoxyterephthalic acid.

[0029] Examples of the aromatic hydroxyamine include 4-aminophenol, N-methyl-4-aminophenol, 3-aminophenol, 3-methyl-4-aminophenol, 2-chloro-4-aminophenol, 4-amino-1-naphthol, 4-amino-4'-hydroxybiphenyl, 4-amino-4'-hydroxydiphenyl ether, 4-amino-4'-hydroxydiphenylmethane, and 4-amino-4'-hydroxydiphenyl sulfide. Examples of the aromatic diamine include 1,4-phenylenediamine, N-methyl-1,4-phenylenediamine, N,N'-dimethyl-1,4-phenylenediamine, 4,4'-diaminophenyl sulfide (thiodianiline), 4,4'-diaminodiphenyl sulfone, 2,5-diaminotoluene, 4,4'-ethylenedianiline, 4,4'-diaminodiphenoxyethane, 4,4'-diaminodiphenylmethane (methylenedianiline), and 4,4'-diaminodiphenyl ether (oxydianiline).

[0030] The aromatic polyester is more preferably an aromatic polyester having the aromatic hydroxycarboxylic acid as a constituent component, and the aromatic polyester amide is more preferably an aromatic polyester amide having the aromatic hydroxycarboxylic acid as a constituent component.

[0031] The method for producing the liquid crystal polymer is not particularly limited, and can be obtained by using various known means. Specifically, for example, the liquid crystal polymer can be produced by known methods such as direct polymerization or transesterification using the above-mentioned raw material monomer compound (or a mixture of raw material monomers). Usually, melt polymerization, solution polymerization, slurry polymerization, solid phase polymerization, or a combination of two or more of these is used, and melt polymerization or a combination of melt polymerization and solid phase polymerization is preferably used. In the case of a compound having an ester forming ability, it may be used in the polymerization in its original form, or it may be used after being modified from a precursor to a derivative having an ester forming ability using an acylating agent or the like in a stage prior to polymerization. Examples of the acylating agent include carboxylic anhydrides such as acetic anhydride.

[0032] In the polymerization, various catalysts may be used. Examples of the catalyst include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, and tris(2,4-pentanedionato)cobalt(III), and organic compound catalysts such as N-methylimidazole and 4-dimethylaminopyridine. The amount of the catalyst used is usually about 0.001 to 1 mass% relative to the total mass of the monomers, and is preferably about 0.01 to 0.2 mass%.

[0033] The liquid crystal polymer is preferably a liquid crystal polyester from the viewpoint of low dielectric properties, heat resistance, and high strength of the resin composition, and from the same viewpoint, a wholly aromatic polyester is more preferable.

[0034] (Physical properties of the above liquid crystal polymer) The physical properties of the liquid crystal polymer are not particularly limited. The melting point (Tm2) of the liquid crystal polymer measured by a differential scanning calorimeter is 250°C or more and 400°C or less, preferably 260°C or more and 380°C or less, and more preferably 280°C or more and 350°C or less.

[0035] The melting point (Tm2) is the peak top temperature of the endothermic peak observed when heating from room temperature at a heating rate of 20°C / min (1st RUN) according to a method based on JIS K-7121 (1999), measuring the peak top temperature (melting point (Tm1)), holding at (melting point (Tm1)+40)°C for 2 minutes, then cooling to room temperature at a heating rate of 20°C / min, and heating again from room temperature at a heating rate of 20°C / min (2nd RUN).

[0036] The liquid crystal polymer may contain various fibrous, powdery, or plate-like inorganic and organic fillers as necessary, as long as the effects of the present invention are not impaired. The inorganic and organic fillers may be used alone or in combination of two or more.

[0037] (Polyphenylene ether resin) The polyphenylene ether resin is not particularly limited, and various known polyphenylene ether resins can be used. The polyphenylene ether resins may be used alone or in combination of two or more.

[0038] The polyphenylene ether resin may be, for example, a homopolymer or copolymer composed of a repeating unit represented by the following general formula (1).

[0039] [ka] (In formula (1), R1, R2, R3, and R4 each independently represent a hydrogen atom, a halogen atom, an alkyl group which may have a substituent, an alkoxy group, or an aryl group which may have a substituent, and n represents the number of repetitions.)

[0040] Examples of the homopolymer represented by the general formula (1) include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-ethyl-6-n-propyl-1,4-phenylene) ether, poly(2,6-di-n-propyl-1,4-phenylene) ether, poly(2-methyl-6-n-butyl-1,4-phenylene) ether, poly(2-ethyl-6-isopropyl-1,4-phenylene) ether, poly(2-methyl-6-chloroethyl-1,4-phenylene) ether, poly(2-methyl-6-hydroxyethyl-1,4-phenylene) ether, and poly(2,6-dichloro-1,4-phenylene) ether.

[0041] Examples of the copolymer include a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, a copolymer of 2,6-dimethylphenol and o-cresol, and a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol.

[0042] The method for producing the polyphenylene ether resin is not particularly limited, and can be obtained by using various known means.Specific examples thereof include the production methods described in U.S. Pat. Nos. 3,306,874, 3,306,875, 3,257,357, and 3,257,358, JP-A-50-51197, JP-B-52-17880, and JP-B-63-152628.

[0043] The polyphenylene ether resin may contain various other phenylene ether units as partial structures within the scope of the present invention. Examples of the phenylene ether units include 2-(dialkylaminomethyl)-6-methylphenylene ether units and 2-(N-alkyl-N-phenylaminomethyl)-6-methylphenylene ether units. In addition, the polyphenylene ether resin may have a small amount of diphenoquinone or the like bonded to the main chain. Furthermore, it may be a polyphenylene ether resin modified with maleic acid, fumaric acid, chloromaleic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, anhydrides thereof, or unsaturated dicarboxylic acids in which one or two of the two carboxyl groups are esterified, allyl glycidyl ether, glycidyl acrylate, glycidyl methacrylate, stearyl acrylate, styrene, epoxidized natural fats and oils, unsaturated alcohols of the general formula CH-3OH (n is a positive integer) such as allyl alcohol, 4-penten-1-ol, and 1,4-pentadiene-3-ol, or unsaturated alcohols of the general formula CH-5OH, CH-7OH (n is a positive integer), etc. These modified polyphenylene ether resins may be used alone or in combination of two or more. The melting point of the modified polyphenylene ether resin is defined as the peak-top temperature of a peak observed in a temperature-heat flow graph obtained when the temperature is raised at a rate of 20°C / min in a measurement using a differential scanning calorimeter (DSC), and when there are multiple peak-top temperatures, the melting point is defined as the highest temperature among them.

[0044] The polyphenylene ether resin may contain a resin component other than polyphenylene ether, such as an aromatic vinyl polymer, polyamide, etc. Examples of the aromatic vinyl polymer include atactic polystyrene, high impact polystyrene, syndiotactic polystyrene, styrene-maleic anhydride copolymer, styrene-butadiene copolymer, and acrylonitrile-styrene copolymer.

[0045] When the polyphenylene ether resin is a mixture containing polyphenylene ether and polystyrene (so-called modified polyphenylene ether resin), the content of polyphenylene ether is usually 70 mass% or more, and preferably 80 mass% or more, based on the total amount of polyphenylene ether and polystyrene.

[0046] Commercially available modified polyphenylene ether resins include, for example, "Iupiace" (registered trademark) manufactured by Mitsubishi Engineering Plastics Corporation, "NORYL" (registered trademark) manufactured by SABIC, and "Zylon" (registered trademark) manufactured by Asahi Kasei Corporation.

[0047] The polyphenylene ether resin may contain various fibrous, powdery, or plate-like inorganic and organic fillers as necessary, as long as the effects of the present invention are not impaired. The inorganic and organic fillers may be used alone or in combination of two or more kinds.

[0048] (Polyphenylene sulfide resin) The polyphenylene sulfide resin is not particularly limited, and various known polyphenylene sulfide resins can be used. The polyphenylene sulfide resins may be used alone or in combination of two or more.

[0049] The polyphenylene sulfide resin may be, for example, a polymer having a repeating unit represented by the following structural formula.

[0050] [ka]

[0051] The polyphenylene sulfide resin is preferably a polymer containing 70 mol % or more, particularly 90 mol % or more, of the repeating unit represented by the above structural formula in terms of heat resistance. In addition, examples of the phenylene group in the above structural formula include p-phenylene, m-phenylene, o-phenylene, alkyl-substituted phenylene (preferably an alkyl group having 1 to 6 carbon atoms), phenyl-substituted phenylene, halogen-substituted phenylene, amino-substituted phenylene, amide-substituted phenylene, p,p'-diphenylene sulfone, p,p'-biphenylene, p,p'-biphenylene ether, p,p'-biphenylene carbonyl, and naphthalene. The polyphenylene sulfide resin containing these phenylene groups may be a homopolymer containing the same repeating unit, a copolymer containing two or more different phenylene groups, or a mixture thereof.

[0052] Furthermore, the polyphenylene sulfide resin may be configured such that less than 30 mol % of the repeating units are repeating units having the following structures:

[0053] [ka]

[0054] The method for producing the polyphenylene sulfide resin is not particularly limited, and can be obtained by using various known means. Specifically, for example, it can be produced by using a polyhalogenated aromatic compound and a sulfidizing agent to obtain a polymer having a relatively small molecular weight as described in JP-B-45-3368, or by using a method for obtaining a polymer having a relatively large molecular weight as described in JP-B-52-12240 and JP-A-61-7332. In addition, it is of course possible to use the polyphenylene sulfide resin obtained as described above after subjecting it to various treatments such as crosslinking / polymerization by heating in air, heat treatment under an inert gas atmosphere such as nitrogen or under reduced pressure, washing with an organic solvent, hot water, an acid aqueous solution, or activation with a functional group-containing compound such as an acid anhydride, an amine, an isocyanate, or a functional group-containing disulfide compound.

[0055] Examples of the polyhalogenated aromatic compound include p-dichlorobenzene, m-dichlorobenzene, o-dichlorobenzene, 1,3,5-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2,4,5-tetrachlorobenzene, hexachlorobenzene, 2,5-dichlorotoluene, 2,5-dichloro-p-xylene, 1,4-dibromobenzene, 1,4-diiodobenzene, 1-methoxy-2,5-dichlorobenzene, etc., and preferably p-dichlorobenzene is used. Also, it is possible to combine two or more different polyhalogenated aromatic compounds to form a copolymer, but it is preferable to use p-dihalogenated aromatic compound as the main component.

[0056] Examples of the sulfidizing agent include alkali metal sulfides, alkali metal hydrosulfides, and hydrogen sulfide. Examples of the alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more of these, with sodium sulfide being preferred. Examples of the alkali metal hydrosulfides include sodium hydrosulfide, potassium hydrosulfide, lithium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more of these, with sodium hydrosulfide being preferred. These alkali metal sulfides and hydrosulfides can be used as hydrates or aqueous mixtures, or in the form of anhydrides. The sulfidizing agents may be used alone or in combination of two or more.

[0057] In addition, the sulfidizing agent may also be an alkali metal sulfide prepared from an alkali metal hydrosulfide and an alkali metal hydroxide; or an alkali metal sulfide prepared from an alkali metal hydroxide such as lithium hydroxide or sodium hydroxide and hydrogen sulfide.

[0058] It is also possible to use an alkali metal hydroxide and / or an alkaline earth metal hydroxide together with the sulfidizing agent. Preferred examples of the alkali metal hydroxide include sodium hydroxide, potassium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide, and mixtures of two or more of these. Preferred examples of the alkaline earth metal hydroxide include calcium hydroxide, strontium hydroxide, barium hydroxide, and the like. Of these, sodium hydroxide is preferably used.

[0059] Commercially available polyphenylene sulfide resins include, for example, "TORELINA" (registered trademark) manufactured by Toray Industries, Inc., "DIC.PPS" (registered trademark) manufactured by DIC Corporation, and "DURAFIDE" (registered trademark) manufactured by Polyplastics Co., Ltd.

[0060] (Physical properties of polyphenylene sulfide resin) The physical properties of the polyphenylene sulfide resin are not particularly limited. The melting point (Tm(A)) of the polyphenylene sulfide resin is preferably 260 to 300°C.

[0061] The melting point (Tm(A)) of the polyphenylene sulfide resin was determined by measuring three times per level using a differential scanning calorimeter (DSC Q2000 manufactured by TA Instruments) by heating the temperature in the range from 25°C to 320°C at a rate of 10°C / min, and calculating the arithmetic mean value of the peak top temperatures of the largest endothermic peaks in the obtained DSC curves.

[0062] The polyphenylene sulfide resin may contain various fibrous, powdery, or plate-like inorganic and organic fillers as necessary, as long as the effects of the present invention are not impaired. The inorganic and organic fillers may be used alone or in combination of two or more.

[0063] (Polybutylene terephthalate resin) The polybutylene terephthalate resin is not particularly limited, and various known polybutylene terephthalate resins can be used. The polybutylene terephthalate resins may be used alone or in combination of two or more.

[0064] The polybutylene terephthalate resin is a polyester resin having a structure in which terephthalic acid units and 1,4-butanediol units are ester-bonded.

[0065] The polybutylene terephthalate resin may be a polybutylene terephthalate copolymer containing other dicarboxylic acid units and other diol units than terephthalic acid units and 1,4-butanediol units, or may be a mixture of the copolymer and a polybutylene terephthalate homopolymer in which only terephthalic acid units and 1,4-butanediol units are ester-bonded.

[0066] Examples of the other dicarboxylic acids include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, bis(4,4'-carboxyphenyl)methane, anthracenedicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 4,4'-dicyclohexyldicarboxylic acid, and aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, and dimer acid. The copolymerization amount of dicarboxylic acids other than these terephthalic acids in the polybutylene terephthalate resin is preferably less than 10 mol%, more preferably less than 5 mol%, and even more preferably less than 3 mol%.

[0067] Examples of the other diols include aliphatic or alicyclic diols having 2 to 20 carbon atoms, bisphenol derivatives, etc. Specific examples include ethylene glycol, propylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, decamethylene glycol, cyclohexanedimethanol, 4,4'-dicyclohexylhydroxymethane, 4,4'-dicyclohexylhydroxypropane, and ethylene oxide adduct diol of bisphenol A. The copolymerization amount in the case where other diol units are contained in addition to these 1,4-butanediols is preferably less than 10 mol%, more preferably less than 5 mol%, and even more preferably less than 3 mol% of the total segments of the polybutylene terephthalate resin.

[0068] In addition to the above-mentioned bifunctional monomers, the polybutylene terephthalate resin may also contain a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, or trimethylolpropane to introduce a branched structure, or a monofunctional compound such as a fatty acid to adjust the molecular weight.

[0069] The polybutylene terephthalate resin may be a copolymer as described above, but is preferably a polybutylene terephthalate homopolymer.

[0070] The method for producing the polybutylene terephthalate resin is not particularly limited, and can be obtained by using various known means. Specifically, for example, it can be produced by melt-polymerizing a dicarboxylic acid component mainly composed of terephthalic acid or an ester derivative thereof and a diol component mainly composed of 1,4-butanediol in a batch or continuous manner. In addition, after producing a low molecular weight polybutylene terephthalate resin by melt polymerization, it can be further solid-phase polymerized under a nitrogen gas flow or reduced pressure to increase the polymerization degree (or molecular weight) to a desired value.

[0071] The polybutylene terephthalate resin is preferably produced by continuous melt polycondensation of a dicarboxylic acid component mainly composed of terephthalic acid and a diol component mainly composed of 1,4-butanediol.

[0072] The catalyst used in carrying out the esterification reaction may be a conventionally known catalyst, and examples thereof include titanium compounds, tin compounds, magnesium compounds, calcium compounds, etc. Among these, titanium compounds are particularly preferred. Specific examples of titanium compounds as esterification catalysts include titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate.

[0073] (Physical properties of polybutylene terephthalate resin) The physical properties of the polybutylene terephthalate resin are not particularly limited. The polybutylene terephthalate resin preferably has a melting point of 215°C or higher, more preferably 220°C or higher, and even more preferably 222°C or higher. The melting point is preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower.

[0074] The melting point of the polybutylene terephthalate resin is the melting point (Tm) of the resin measured at a temperature rise rate of 20° C. / min by differential scanning calorimetry (DSC) based on JIS K7121.

[0075] (Physical properties of resin (A)) The physical properties of component (A) are not particularly limited. Component (A) preferably has a dielectric loss tangent tanδ of 0.01 or less at 1 GHz. Component (A) having such low dielectric properties reduces the effect of dielectric loss in the high frequency band (GHz band).

[0076] <Petroleum resin (B)> The component (B) is not particularly limited, and various known components can be used, so long as the 5% weight loss temperature is 270° C. or higher and the mixed methylcyclohexaneaniline cloud point (MMAP) is 10 to 95° C. The component (B) may be used alone or in combination of two or more.

[0077] The resin composition of the present invention has excellent moldability and can maintain the low dielectric properties of the component (A) because the melt viscosity of the resin composition is reduced by using the component (B). Conventional flow improvers can reduce the low dielectric properties of the component (A), but the component (B) itself has low dielectric properties, so that even when used in a resin composition containing the component (A), it can improve the moldability of the resin composition without reducing the low dielectric properties of the component (A).

[0078] Examples of the (B) component include various known petroleum resins. Examples of the petroleum resins include aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic-aromatic petroleum resins, pure monomer resins, and hydrogenated products thereof (hereinafter, these hydrogenated products are referred to as hydrogenated petroleum resins). The petroleum resins may be used alone or in combination of two or more.

[0079] Examples of the aliphatic petroleum resin include C5 petroleum resins obtained from C5 petroleum fractions of naphtha. Examples of the C5 petroleum fraction include conjugated diolefinic unsaturated hydrocarbons having 4 to 6 carbon atoms, such as isoprene, trans-1,3-pentadiene, cis-1,3-pentadiene, cyclopentadiene, and methylcyclopentadiene; monoolefinic unsaturated hydrocarbons having 4 to 6 carbon atoms, such as butene, 2-methyl-1-butene, 2-methyl-2-butene, 1-pentene, 2-pentene, and cyclopentene; aliphatic saturated hydrocarbons, such as cyclopentane, 2-methylpentane, 3-methylpentane, and n-hexane; and mixtures thereof.

[0080] Examples of the alicyclic petroleum resin include dicyclopentadiene petroleum resins obtained from cyclopentadiene petroleum fractions of naphtha. Examples of the cyclopentadiene petroleum fraction include cyclopentadiene, methylcyclopentadiene, ethylcyclopentadiene, and their dimers, trimers, co-dimers, and mixtures thereof. Examples of the dimer include dicyclopentadiene.

[0081] Examples of the aromatic petroleum resin include C9 petroleum resins obtained from C9 petroleum fractions of naphtha, copolymers obtained by polymerizing the C9 petroleum resins alone or in combination, etc. Examples of the C9 petroleum fraction include aromatic compounds having 8 carbon atoms such as styrene, aromatic compounds having 9 carbon atoms such as α-methylstyrene, β-methylstyrene, vinyltoluene, and indene, aromatic compounds having 10 carbon atoms such as 2-isopropenyltoluene, 4-isopropenyltoluene, 1-methylindene, 2-methylindene, and 3-methylindene, aromatic compounds having 11 carbon atoms such as 2,3-dimethylindene and 2,5-dimethylindene, and mixtures thereof.

[0082] Examples of the aliphatic / aromatic petroleum resin include C5 / C9 copolymer petroleum resins obtained from the above C5 petroleum fraction and C9 petroleum fraction.

[0083] Examples of the alicyclic / aromatic petroleum resins include cyclopentadiene / C9 copolymer petroleum resins obtained from the cyclopentadiene petroleum fractions and C9 petroleum fractions, and specific examples thereof include dicyclopentadiene / styrene copolymer petroleum resins and dicyclopentadiene / C9 copolymer petroleum resins.

[0084] Examples of the pure monomer resin include resins obtained by polymerizing polymerizable monomers (styrene, vinyltoluene, α-methylstyrene, isopropenyltoluene, indene) obtained by refining the C9 petroleum fraction by cationic polymerization, radical polymerization, or the like.

[0085] The hydrogenated petroleum resins can be obtained by various known means, specifically, for example, by hydrogenating the various petroleum resins (aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic-aromatic petroleum resins, and pure monomer resins) under known hydrogenation conditions.

[0086] The hydrogenation conditions include, for example, a method in which the above-mentioned various petroleum resins (aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic-aromatic petroleum resins, and pure monomer resins) are heated to about 200 to 350° C. under a hydrogen partial pressure of about 0.2 to 30 MPa in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include metals such as nickel, palladium, cobalt, ruthenium, platinum, and rhodium, and oxides of these metals. The amount of the hydrogenation catalyst used is preferably usually about 0.01 to 10 parts by mass per 100 parts by mass of the raw material resin.

[0087] The hydrogenation is carried out by melting the various petroleum resins (aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic petroleum resins, alicyclic-aromatic petroleum resins, pure monomer resins) or dissolving them in a solvent. The solvent for dissolving the petroleum resin is not particularly limited, but any solvent that is inert to the reaction and easily dissolves the raw materials and products may be used. For example, cyclohexane, n-hexane, n-heptane, decalin, tetrahydrofuran, dioxane, etc. can be used alone or in combination of two or more. The amount of the solvent used is not particularly limited, but the solid content is usually 10% by mass or more relative to the petroleum resin, and preferably in the range of 10 to 70% by mass. The hydrogenation conditions are described for the case where a batch system is used as the reaction system, but a flow system (fixed bed system, fluidized bed system, etc.) can also be used as the reaction system.

[0088] The hydrogenated petroleum resin is preferably a hydrogenated aromatic petroleum resin, since the resin composition has excellent low dielectric properties.

[0089] The component (B) is preferably a hydrogenated petroleum resin, since this suppresses smoke generation during molding of the resin composition and provides excellent low dielectric properties in the resin composition.

[0090] (Physical properties of petroleum resin (B)) The 5% weight loss temperature (°C) of component (B) is 270°C or higher. In this specification, the 5% weight loss temperature refers to the temperature (°C) at which a 5% weight loss occurs when thermogravimetry is measured under a nitrogen atmosphere using a thermogravimetry / differential thermal analyzer (TG / DTA).

[0091] When the 5% weight loss temperature of component (B) is 270° C. or higher, smoke generation during molding of the resin composition is suppressed.

[0092] The 5% weight loss temperature of component (B) is preferably 290° C. or higher, more preferably 300° C. or higher, and particularly preferably 350° C. or higher, in order to suppress smoke generation during molding of the resin composition.

[0093] In order to increase the 5% weight loss temperature of component (B), it is sufficient to remove low molecular weight components from component (B) and reduce the content of low molecular weight components in component (B). Methods for removing low molecular weight components include, for example, distilling component (B) under reduced pressure, blowing steam into component (B), and recrystallizing component (B) using a good solvent and a poor solvent.

[0094] If the 5% weight loss temperature of component (B) is less than 270° C., a large amount of smoke will be generated during molding of the resin composition.

[0095] The mixed methylcyclohexaneaniline cloud point (MMAP) (°C) of the component (B) is 10 to 95°C. The mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) indicates the aromatic and aliphatic characteristics of the component (B). When the ratio of aromatic parts in the component (B) is high, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be low, and when the ratio of aromatic parts is low, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be high. In addition, when the ratio of aliphatic parts in the component (B) is high, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be high, and when the ratio of aliphatic parts is low, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be low. In this specification, the mixed methylcyclohexaneaniline cloud point (MMAP) is measured by the method described in the examples below.

[0096] Furthermore, when component (B) contains a highly polar functional group such as a hydroxyl group, an amino group, or a carbonyl group, the mixed methylcyclohexaneaniline cloud point (MMAP) also tends to be low.

[0097] When component (B) is an unhydrogenated petroleum resin obtained by using a large amount of aliphatic raw materials such as C5 petroleum fractions and cyclopentadiene-based petroleum fractions, or the above-mentioned hydrogenated petroleum resins, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be high. When component (B) is an unhydrogenated petroleum resin obtained by using a large amount of aromatic raw materials such as C9 petroleum fractions and pure monomers, the mixed methylcyclohexaneaniline cloud point (MMAP) tends to be low.

[0098] When the mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) is within a range from 10 to 95° C., the resin composition has excellent low dielectric properties.

[0099] The mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) is preferably about 80 to 95°C, and more preferably about 85 to 95°C, in view of excellent low dielectric properties in the resin composition.

[0100] If the mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) is less than 10° C., the low dielectric properties of the resin composition will decrease.

[0101] The physical properties of component (B) are not particularly limited except for the 5% weight loss temperature and mixed cyclohexaneaniline cloud point (MMAP). The color tone of component (B) is preferably about 10 to 400 Hazen, more preferably about 10 to 200 Hazen, from the viewpoint of suppressing coloration in the resin composition and molded product. In this specification, the color tone is measured in Hazen units according to JIS K 0071-1, and in Gardner units according to JIS K 0071-2.

[0102] The softening point of the (B) component is preferably about 80 to 190° C. from the viewpoints of suppressing smoke generation during molding of the resin composition and of providing excellent low dielectric properties to the resin composition, and from the same viewpoints, is more preferably about 120 to 190° C., and from the same viewpoints, is particularly preferably about 135 to 190° C. In this specification, the softening point is a value measured by the ring and ball method according to JIS K 5902.

[0103] The higher the softening point of component (B), the higher the 5% weight loss temperature tends to be. Also, the higher the softening point of component (B), the more the molecular motion in component (B) is suppressed, and the more the dielectric loss in component (B) is suppressed, so that the low dielectric properties of the resin composition tend to be more excellent.

[0104] The (B) component may contain various known additives as necessary, so long as they do not impair the effects of the present invention. Examples of additives include dehydrating agents, weathering agents, antioxidants, ultraviolet absorbers, heat stabilizers, and light stabilizers. The above additives may be used alone or in combination of two or more.

[0105] (Filler (C)) The resin composition may contain a filler (C) (hereinafter referred to as component (C)). The component (C) is not particularly limited, and various known ones can be used. The component (C) may be used alone or in combination of two or more.

[0106] The shape of component (C) may be, for example, spherical, needle-like, fibrous, or plate-like.

[0107] Examples of component (C) include fibers, crystalline silica, fused silica, calcium silicate, silica sand, talc, kaolin, mica, clay, bentonite, sericite, calcium carbonate, magnesium carbonate, glass beads, glass flakes, glass microballoons, molybdenum disulfide, wollastonite, calcium polyphosphate, graphite, metal powder, metal flakes, metal ribbons, metal oxides (alumina, zinc oxide, titanium oxide, etc.), carbon powder, graphite, carbon flakes, scaly carbon, carbon nanotubes, etc. Specific examples of metals constituting the metal powder, metal flakes, and metal ribbons include silver, nickel, copper, zinc, aluminum, stainless steel, iron, brass, chromium, tin, etc.

[0108] The above-mentioned fibers are not particularly limited and various known fibers can be used. Examples of the above-mentioned fibers include carbon fibers, glass fibers, alumina fibers, polyester fibers, polyamide fibers, polyimide fibers, polyvinyl alcohol modified fibers, polyvinyl chloride fibers, polyolefin (polyethylene, polypropylene) fibers, fluororesin fibers, polybenzimidazole fibers, acrylic fibers, phenolic fibers, polyamide fibers, aramid fibers, cellulose (nano) fibers, liquid crystal polymer (liquid crystal polyester, liquid crystal polyester amide) fibers, polyether ketone fibers, polyether sulfone fibers, polyphenylene ether fibers, polyphenylene sulfide fibers, and other organic fibers; and metal fibers made of metals such as iron, gold, silver, copper, aluminum, brass, and stainless steel. The above-mentioned fibers may be used alone or in combination of two or more types.

[0109] The fibers preferably include at least one type selected from the group consisting of glass fibers, carbon fibers, and organic fibers.

[0110] The component (C) preferably contains at least one selected from the group consisting of glass fiber and carbon powder, in that the resin composition will have excellent impact resistance.

[0111] In conventional resin compositions containing a filler, the filler can cause the melt viscosity of the resin composition to be very high, resulting in extremely poor moldability. However, the resin composition of the present invention uses component (B) and therefore has a low melt viscosity, even when component (C) is contained, resulting in excellent moldability.

[0112] (Additives) The resin composition may contain additives as necessary, so long as the effects of the present invention are not impaired. Examples of additives include flame retardants, electrical conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, colorants, dyes, foaming agents, foam inhibitors, coupling agents, inorganic pigments, organic pigments, flow improvers other than component (B), and light stabilizers.

[0113] (Content of each ingredient) When the resin composition does not contain the (C) component, the content of the (B) component in the resin composition is not particularly limited, but is preferably 0.1 to 10 parts by mass per 100 parts by mass of the (A) component.

[0114] When the content of component (B) is 0.1 parts by mass or more per 100 parts by mass of component (A), the resin composition has excellent moldability. When the content of component (B) is 10 parts by mass or less per 100 parts by mass of component (A), the resin composition has excellent moldability, smoke generation during molding of the resin composition is further suppressed, and deterioration of the low dielectric properties of the resin composition is further suppressed.

[0115] When the resin composition does not contain the (C) component, the content of the (B) component in the resin composition is more preferably 0.5 to 5 parts by mass per 100 parts by mass of the (A) component, since smoke generation during molding of the resin composition is further suppressed and the resin composition has particularly excellent moldability and low dielectric properties.

[0116] When the resin composition contains the (C) component, the content of the (B) component in the resin composition is not particularly limited, but from the viewpoints of further suppressing smoke generation during molding of the resin composition and providing the resin composition with superior moldability and low dielectric properties, the content is preferably 0.5 to 15 parts by mass, and more preferably 5 to 10 parts by mass, per 100 parts by mass of the (A) component.

[0117] When the resin composition contains the component (C), the content of the component (C) in the resin composition is not particularly limited, but is preferably 60 parts by mass or less per 100 parts by mass of the component (A).

[0118] The content of the additive in the resin composition is not particularly limited, but is usually 0.001 part by mass or more, preferably 0.005 part by mass or more, and more preferably 0.01 part by mass or more, relative to 100 parts by mass of the resin composition, and is usually 100 parts by mass or less, and preferably 50 parts by mass or less.

[0119] (Method of producing resin composition) The method for producing the resin composition is not particularly limited, and various known methods can be used. For example, the method for producing the resin composition includes a method in which the (A) component, the (B) component, and if necessary, the (C) component and the above additives are mixed in advance using various mixers such as a tumbler mixer or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The temperature for the melt-kneading is not particularly limited, but is usually in the range of the melting point of the (A) component -30°C to the melting point +30°C.

[0120] [Molded body] The molded article of the present invention can be obtained by molding the resin composition by various known molding methods. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, polygonal, irregular, hollow, frame-like, box-like, and panel-like shapes.

[0121] The method for molding the molded body is not particularly limited, and a conventionally known molding method can be used.Specific examples include injection molding, injection compression molding, extrusion molding, stretch film molding, inflation molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), press molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.Among them, molding is preferably performed by injection molding.As the injection molding machine, known injection molding machines such as ultra-high speed injection molding machines and injection compression molding machines can be mentioned.

[0122] The molded article of the present invention can be used for various purposes such as automobile parts, electric / electronic parts, building materials, various containers, daily necessities, household goods, and sanitary products. In addition, since the molded article of the present invention has excellent low dielectric properties, it is particularly useful for electric / electronic parts and automobile parts corresponding to high frequencies such as wireless LAN, ETC, satellite communication antennas, and vehicle-mounted radar. In addition, it is useful for molded articles (metal composite molded articles) that are used in combination with metal parts by insert molding, and such metal composite molded articles can be suitably used for mobile communication device parts.

[0123] [Flow improver] The fluidity improver of the present invention contains the above-mentioned (B) component. The fluidity improver of the present invention is used in a low dielectric resin to maintain the low dielectric properties of the low dielectric resin while reducing the melt viscosity of the low dielectric resin and improving its molding processability. Note that the fluidity improver of the present invention is different from the above-mentioned resin composition.

[0124] The flowability improver can be used for various known low dielectric resins. The low dielectric resins may be used alone or in combination of two or more.

[0125] The low dielectric resin preferably has a dielectric loss tangent tan δ of 0.01 or less at 1 GHz. By having such low dielectric properties, the low dielectric resin is less susceptible to the influence of dielectric loss in the high frequency band (GHz band).

[0126] As the low dielectric resin, the above-mentioned component (A) is preferred because of its low dielectric properties, heat resistance and high strength.

[0127] The component (B) in the flow improver is preferably a hydrogenated petroleum resin, since it suppresses smoke generation during molding of the low dielectric resin and suppresses deterioration of the low dielectric properties of the low dielectric resin.

[0128] The 5% weight loss temperature of the component (B) in the above flow improver is 270° C. or higher. In this specification, the 5% weight loss temperature is the temperature at which the weight is reduced by 5% when the thermogravimetry is measured under a nitrogen atmosphere using a thermogravimetry / differential thermal analyzer (TG / DTA).

[0129] When the 5% weight loss temperature of the component (B) in the flow improver is 270° C. or higher, smoke emission during molding of the low dielectric resin is suppressed.

[0130] The 5% weight loss temperature of the (B) component in the above-mentioned flow improver is preferably 290°C or higher, more preferably 300°C or higher, and particularly preferably 350°C or higher, from the viewpoint of suppressing smoke generation during molding of the low dielectric resin.

[0131] In order to increase the 5% weight loss temperature of the (B) component in the above-mentioned flow improver, the low molecular weight components may be removed from the (B) component to reduce the content of the low molecular weight components in the (B) component. Examples of methods for removing the low molecular weight components include distilling the (B) component under reduced pressure, blowing steam into the (B) component, and recrystallizing the (B) component using a good solvent and a poor solvent.

[0132] If the 5% weight loss temperature of the component (B) in the flow improver is less than 270° C., a large amount of smoke is generated during molding of the low dielectric resin.

[0133] The mixed methylcyclohexaneaniline cloud point (MMAP) (° C.) of the component (B) in the above flow improver is 10 to 95° C. In this specification, the mixed methylcyclohexaneaniline cloud point (MMAP) is measured by the method described in the Examples below.

[0134] When the mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) in the flow improver is 10 to 95° C., the deterioration of the low dielectric properties of the low dielectric resin is suppressed.

[0135] The mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) in the above flow improver is preferably about 80 to 95°C, more preferably about 85 to 95°C, in order to suppress a decrease in the low dielectric properties of the low dielectric resin.

[0136] When the mixed methylcyclohexaneaniline cloud point (MMAP) of the component (B) in the flow improver is less than 10° C., the low dielectric properties of the low dielectric resin are reduced.

[0137] The physical properties of the (B) component in the flow improver are not particularly limited except for the 5% weight loss temperature and mixed cyclohexaneaniline cloud point (MMAP). The color tone of the (B) component is preferably about 10 to 400 Hazen, more preferably about 10 to 200 Hazen, from the viewpoint of suppressing coloration in molded products of low dielectric resins. In this specification, the color tone is measured in Hazen units according to JIS K 0071-1, and in Gardner units according to JIS K 0071-2.

[0138] The softening point of the (B) component in the flow improver is preferably about 80 to 190° C. from the viewpoint of suppressing smoke generation during molding of the low dielectric resin and further suppressing the deterioration of the low dielectric properties of the low dielectric resin, more preferably about 120 to 190° C. from the same viewpoint, and particularly preferably about 135 to 190° C. from the same viewpoint. In this specification, the softening point is a value measured by the ring and ball method of JIS K 5902.

[0139] The higher the softening point of the (B) component in the flow improver, the higher the 5% weight loss temperature tends to be. Also, the higher the softening point of the (B) component in the flow improver, the more the molecular motion in the (B) component is suppressed, and the more the dielectric loss is suppressed, so that the degradation of the low dielectric properties of the low dielectric resin tends to be suppressed.

[0140] The amount of the flow improver used is not particularly limited, but is preferably 0.1 to 10 parts by mass with respect to 100 parts by mass of the low dielectric resin.

[0141] When the amount of the flow improver used is 0.1 parts by mass or more relative to 100 parts by mass of the low dielectric resin, the molding processability of the low dielectric resin is further improved. When the amount of the flow improver used is 10 parts by mass or less relative to 100 parts by mass of the low dielectric resin, the molding processability of the low dielectric resin is further improved, smoke generation during molding of the low dielectric resin is further suppressed, and deterioration of the low dielectric properties of the low dielectric resin is further suppressed.

[0142] The amount of the flow improver used is preferably 0.5 to 5 parts by mass relative to 100 parts by mass of the low dielectric resin, from the viewpoints of further suppressing smoke generation during molding of the low dielectric resin, further improving the molding processability of the low dielectric resin, and further suppressing deterioration of the low dielectric properties of the low dielectric resin.

[0143] Furthermore, when a filler such as component (C) is used in combination with the low dielectric resin, the amount of the flow improver used is not particularly limited, but from the viewpoints of further suppressing smoke generation during molding of the low dielectric resin, further improving the molding processability of the low dielectric resin, and further suppressing deterioration of the low dielectric properties of the low dielectric resin, it is preferably 0.5 to 15 parts by mass, and more preferably 5 to 10 parts by mass, relative to 100 parts by mass of the low dielectric resin.

[0144] The fluidity improver of the present invention may contain various known additives as necessary, as long as the effects of the present invention are not impaired. Examples of additives include dehydrating agents, weathering agents, antioxidants, ultraviolet absorbers, heat stabilizers, and light stabilizers. The above additives can be used alone or in combination of two or more. The content of the above additives is not particularly limited, but is preferably 0.5 to 10 parts by mass relative to 100 parts by mass of the fluidity improver.

[0145] The method of using the fluidity improver of the present invention is not particularly limited. For example, the method of using the fluidity improver includes adding the fluidity improver together with the low dielectric resin to a mixer and melt-kneading the mixture with the mixer. For example, the mixer includes a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, etc. The temperature of the melt-kneading is not particularly limited, but is usually in the range of the melting point of the low dielectric resin -30°C to the melting point +30°C. EXAMPLES

[0146] The present invention will be described in more detail below by showing examples of the present invention. The present invention is not limited to the examples. In the examples, "parts" and "%" respectively represent the following. The terms "parts by mass" and "% by mass" are used.

[0147] (Production of hydrogenated petroleum resin (B)) Manufacturing Example 1 100 parts of C9 petroleum resin (color tone 10 Gardner, softening point 140°C) and 0.4 parts of a catalyst (nickel content 55% by weight, catalyst surface area 350m2 / g, bulk specific gravity 0.30g / cm3) prepared by hydrogen reduction of nickel-synthetic silica alumina catalyst oxide prepared by precipitation method at 400°C under hydrogen flow for 1 hour were subjected to hydrogenation reaction in a shaking autoclave under the conditions of hydrogen partial pressure 19.6MPa, reaction temperature 290°C, and reaction time 6 hours. After the reaction was completed, the obtained resin was dissolved in 400 parts of cyclohexane, and the catalyst was removed by filtration. Thereafter, the filtrate was placed in a 1-liter separable flask equipped with a stirring blade, a condenser, a thermometer, a temperature regulator, and a pressure indicator, and the temperature and pressure were gradually increased and reduced to 200°C and 2.7kPa to remove the solvent, and 99 parts of hydrogenated C9 petroleum resin (hereinafter referred to as (B1) component) with a softening point of 139°C and a color tone of 20 Hazen was obtained.

[0148] Manufacturing Example 2 100 parts of C9 petroleum resin (color tone 10 Gardner, softening point 125°C) and 0.4 parts of a catalyst (nickel content 55% by weight, catalyst surface area 350m2 / g, bulk specific gravity 0.30g / cm3) prepared by hydrogen reduction of nickel-synthetic silica alumina catalyst oxide prepared by precipitation method at 400°C for 1 hour under hydrogen flow were subjected to hydrogenation reaction in a shaking autoclave under the conditions of hydrogen partial pressure 19.6MPa, reaction temperature 305°C, and reaction time 5 hours. After the reaction was completed, the obtained resin was dissolved in 400 parts of cyclohexane, and the catalyst was removed by filtration. Thereafter, the filtrate was placed in a 1-liter separable flask equipped with a stirring blade, a condenser, a thermometer, a temperature regulator, and a pressure indicator, and the temperature and pressure were gradually increased and reduced to 200°C and 2.7kPa to remove the solvent, and 101 parts of hydrogenated C9 petroleum resin (hereinafter referred to as (B2) component) with a softening point of 125°C and a color tone of 20 Hazen was obtained.

[0149] Production Example 3 In Production Example 2, the same operation as in Production Example 1 was carried out except that the reaction temperature was 305°C, and 101 parts of a hydrogenated C9 petroleum resin (hereinafter referred to as component (B3)) having a softening point of 115°C and a color tone of 15 Hazen was obtained.

[0150] Production Example 4 100 parts of C9 petroleum resin (color tone 10 Gardner, softening point 140°C) and nickel-synthetic silica-alumina catalytic oxide prepared by precipitation method were hydrogen-reduced under a hydrogen stream at 400°C for 1 hour to form a catalyst (nickel content 55% by weight, catalyst surface area 350 m 2 / g, bulk density 0.30g / cm 3 0.35 parts of the above was subjected to a hydrogenation reaction in a shaking autoclave under conditions of a hydrogen partial pressure of 19.6 MPa, a reaction temperature of 280°C, and a reaction time of 5 hours. After completion of the reaction, the obtained resin was dissolved in 400 parts of cyclohexane, and the catalyst was removed by filtration. The obtained filtrate was then placed in a 1-liter separable flask equipped with a stirring blade, a condenser, a thermometer, a temperature regulator, and a pressure indicator, and the temperature and pressure were gradually increased and reduced to 200°C and 2.7 kPa, respectively, to remove the solvent, yielding 101 parts of a hydrogenated C9 petroleum resin (hereinafter referred to as component (B4)) having a softening point of 135°C and a color tone of 30 Hazen.

[0151] Production Example 5 100 parts of the hydrogenated C9 petroleum resin obtained in Production Example 1 was heated to 260°C, and water vapor at normal pressure (0.1 MPa) was blown in for 4 hours to remove moisture and the like under reduced pressure, yielding 90 parts of hydrogenated C9 petroleum resin (hereinafter referred to as component (B5)) having a softening point of 157°C and a color tone of 20 Hazen as the residue.

[0152] Production Example 6 100 parts of the hydrogenated C9 petroleum resin obtained in Production Example 1 was dissolved in 250 parts of 2-ethylhexanol. After dissolution, 250 parts of 2-propanol was added dropwise to obtain 30 parts of hydrogenated C9 petroleum resin (hereinafter referred to as component (B6)) having a softening point of 182° C. and a color tone of 20 Hazen as a precipitate.

[0153] Comparative Manufacturing Example 1 A 1L autoclave was charged with 500 parts of hydroxyl-containing dicyclopentadiene-based petroleum resin (trade name "Quinton 1700", a reaction product of dicyclopentadiene and allyl alcohol, manufactured by Zeon Corporation, softening point 102°C) and 7 parts of nickel / diatomaceous earth catalyst (nickel loading 50% by mass), and hydrogenation was carried out for 5 hours at 280°C and a hydrogen pressure of 20 MPa. Next, the obtained hydrogenated product of the hydroxyl-containing dicyclopentadiene-based petroleum resin was taken out and dissolved in 500 parts of toluene. After removing the catalyst by filtration, the solvent was removed under reduced pressure at 200°C and 2.7 kPa for 30 minutes to obtain 450 parts of hydrogenated product of the hydroxyl-containing dicyclopentadiene-based petroleum resin (hereinafter referred to as component (b3)). The component (b3) had a softening point of 110°C and a color tone of 200 Hazen.

[0154] (color tone) The color tones of the components (B1) to (B6), the component (B7) and the component (b3) described below, and the components (b1), (b2) and (b4) described below were measured in accordance with JIS K 0071-1 for the Hazen unit and in accordance with JIS K 0071-2 for the Gardner unit.

[0155] (softening point) The softening points of the components (B1) to (B6), the component (B7) and the component (b3) described below, and the components (b1), (b2) and (b4) described below were measured in accordance with JIS K 5902.

[0156] (Measurement of 5% weight loss temperature) The 5% weight loss temperatures of components (B1) to (B6), components (B7) and (b3) described below, and components (b1), (b2) and (b4) described below were measured using a simultaneous differential thermal and gravimetric analyzer (manufactured by Hitachi High-Tech Science Corporation, device name "STA7200") under a nitrogen atmosphere with a sample weight of 10 mg at a measurement temperature of 30 to 500°C, a heating rate of 10°C / min and a nitrogen flow rate of 250 ml / min. The results are shown in Tables 1 to 3.

[0157] (Measurement of mixed methylcyclohexaneaniline cloud point (℃) (MMAP)) The methylcyclohexaneaniline cloud point (℃) (MMAP) of the mixture of the components (B1) to (B6), the component (B7) and the component (b3) described below, and the components (b1), (b2) and (b4) described below was measured by cooling a heated homogeneous solution of 1 g of each component, 1 mL of methylcyclohexane and 2 mL of aniline, and measuring the temperature at which the solution became cloudy. The results are shown in Tables 1 to 3.

[0158] [Preparation of resin composition] Example 1 100 parts of liquid crystal polyester (manufactured by Polyplastics Co., Ltd., product name "LAPEROS C950RX") (hereinafter referred to as component (A1)) and 2 parts of component (B1) were put into a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 350°C. Thereafter, the kneaded product (resin composition) obtained was taken out of the kneading device, hot pressed at 350°C, and molded into a sheet having a thickness of 1.0 mm to obtain a sheet-like molded product. In addition, a part of the sheet-like molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0159] Example 2 The same preparation as in Example 1 was carried out except that 2 parts of the component (B2) was used instead of the component (B1) in Example 1, to obtain a sheet-shaped molding and pellets.

[0160] Example 3 The same preparation as in Example 1 was carried out except that 2 parts of the component (B3) was used instead of the component (B1) in Example 1, to obtain a sheet-shaped molding and pellets.

[0161] Example 4 The same preparation as in Example 1 was carried out except that 2 parts of the component (B4) was used instead of the component (B1) in Example 1, to obtain a sheet-shaped molding and pellets.

[0162] Example 5 The same preparation as in Example 1 was carried out except that 2 parts of the component (B5) was used instead of the component (B1) in Example 1, to obtain a sheet-shaped molding and pellets.

[0163] Example 6 The same preparation as in Example 1 was carried out except that 2 parts of the component (B6) was used instead of the component (B1) in Example 1, to obtain a sheet-shaped molding and pellets.

[0164] Example 7 In Example 1, except that 2 parts of a C9 petroleum resin (hereinafter referred to as (B7) component) having a softening point of 145°C, a color tone of 10 Gardner, a 5% weight loss temperature of 302°C, and an MMAP of 12°C was used instead of the (B1) component, preparation was performed in the same manner as in Example 1 to obtain a sheet-shaped molded product and pellets.

[0165] Example 8 Preparation was carried out in the same manner as in Example 1, except that 100 parts of a liquid crystal polyester (manufactured by Polyplastics Co., Ltd., product name "LAPEROS A950RX") (hereinafter referred to as "component (A2)") was used instead of the component (A1) in Example 1, to obtain a sheet-shaped molded product and pellets.

[0166] Comparative Example 1 100 parts of component (A1) were added to a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 5 minutes at a roller rotation speed of 40 rpm and a temperature of 350°C. The kneaded product obtained was then removed from the kneading device and heat pressed at 350°C to form a sheet having a thickness of 1.0 mm, thereby obtaining a sheet-like molded product. A part of the sheet-like molded product was cut into 5 mm x 5 mm pieces using a cutter to obtain pellets.

[0167] Comparative Example 2 A sheet-shaped molding and pellets were obtained in the same manner as in Comparative Example 1, except that 100 parts of the component (A2) were used instead of the component (A1).

[0168] Comparative Example 3 In Example 1, except that 2 parts of hydrogenated C9 petroleum resin (manufactured by Arakawa Chemical Industries, Ltd., product name "Arcon P-100", softening point 103°C, color tone 20 Hazen) (hereinafter referred to as (b1) component) were used instead of the (B1) component, preparation was performed in the same manner as in Example 1 to obtain a sheet-shaped molding and pellets.

[0169] Comparative Example 4 In Example 1, except that 2 parts of hydrogenated C9 petroleum resin (manufactured by Arakawa Chemical Industries, Ltd., product name "Arcon P-90", softening point 90°C, color tone 20 Hazen) (hereinafter referred to as (b2) component) were used instead of the (B1) component, preparation was performed in the same manner as in Example 1 to obtain a sheet-shaped molding and pellets.

[0170] (Smoke generation evaluation) The pellets of Examples 1 to 8 and Comparative Examples 1 to 4 were injection molded at 350°C using a Handtruder M-1 (a tabletop manual injection molding machine / pelletizer manufactured by Toyo Seiki Seisakusho Co., Ltd.), and smoke generation during molding was visually evaluated and rated according to the following criteria. The results are shown in Table 1. ○: Almost no smoke. △: A small amount of smoke is produced. ×: A lot of smoke is emitted.

[0171] (Evaluation of dielectric tangent) Using a network analyzer (Keysight Technologies, device name "P5003A") and a split post dielectric resonator (QWED) with a measurement frequency of 10.124 GHz, the resonant frequency and peak Q value of the resonator alone with nothing inserted were measured. Next, the sheet-shaped molded products of Examples 1 to 8 and Comparative Examples 1 to 4 were inserted into the resonators, and then the resonance frequency and Q value were measured when the sheet-shaped molded products were inserted. The dielectric loss tangent (Df) of the sheet-shaped molded products of Examples 1 to 8 and Comparative Examples 1 to 4 was calculated from the difference in Q value and the difference in resonance frequency between the resonator alone and when the sheet-shaped molded product was inserted.

[0172] The rate of increase in the dielectric loss tangent (Df) of the sheet-form moldings of Examples 1 to 7 and Comparative Examples 3 and 4 relative to the dielectric loss tangent (Df) of Comparative Example 1 (blank) was evaluated according to the following criteria. The rate of increase in the dielectric loss tangent (Df) of the sheet-form moldings of Example 8 relative to the dielectric loss tangent (Df) of Comparative Example 2 (blank) was also evaluated according to the following criteria. The results are shown in Table 1. The smaller the rate of increase in the dielectric loss tangent (Df), the more excellent the low dielectric properties. ○: The increase in dielectric tangent compared to the blank is less than 10% △: The increase in dielectric tangent compared to blank is 10% to 30%. ×: The increase in dielectric tangent compared to the blank is 30% or more.

[0173] (Evaluation of Melt Viscosity) For the pellets of Examples 1 to 8 and Comparative Examples 1 to 4, the apparent melt viscosity at a temperature of 330°C and a shear rate of 2432 (1 / sec) was measured in accordance with JIS K7199 using a commercially available capillary rheometer (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Capillograph 1C").

[0174] The melt viscosity reduction rate of the pellets of Examples 1 to 7 and Comparative Examples 3 and 4 relative to the melt viscosity of Comparative Example 1 (blank) was evaluated according to the following criteria. The melt viscosity reduction rate of the pellets of Example 8 relative to the melt viscosity of Comparative Example 2 (blank) was also evaluated according to the following criteria. The results are shown in Table 1. The larger the melt viscosity reduction rate, the more excellent the molding processability. ○: The decrease in melt viscosity compared to the blank is 10% or more. △: The decrease in melt viscosity compared to the blank is 3% or more but less than 10%. ×: The decrease in melt viscosity compared to the blank is less than 3%.

[0175] [Table 1]

[0176] The blending amounts in Table 1 are given in parts by mass.

[0177] [Preparation of resin composition] Example 9 100 parts of modified polyphenylene ether resin (manufactured by Mitsubishi Engineering Plastics Corporation, product name "Iupiace AH40") (hereinafter referred to as component (A3)) and 5 parts of component (B1) were put into a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 250°C. Thereafter, the kneaded product (resin composition) obtained was taken out of the kneading device, hot pressed at 250°C, and molded into a sheet having a thickness of 1.0 mm to obtain a sheet-like molded product. A part of the sheet-like molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0178] Example 10 A sheet-like molding and pellets were obtained in the same manner as in Example 9, except that 5 parts of the component (B2) were used instead of the component (B1).

[0179] Example 11 A sheet-shaped molding and pellets were obtained in the same manner as in Example 9, except that 5 parts of the component (B4) were used instead of the component (B1).

[0180] Example 12 A sheet-like molding and pellets were obtained in the same manner as in Example 9, except that 5 parts of the component (B5) were used instead of the component (B1).

[0181] Example 13 A sheet-like molding and pellets were obtained in the same manner as in Example 9, except that 5 parts of the component (B6) were used instead of the component (B1).

[0182] Example 14 A sheet-like molding and pellets were obtained in the same manner as in Example 9, except that 5 parts of the component (B7) were used instead of the component (B1).

[0183] Comparative Example 5 100 parts of component (A3) were added to a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 250°C. The kneaded product obtained was then removed from the kneading device and hot pressed at 250°C to form a sheet having a thickness of 1.0 mm, thereby obtaining a sheet-like molded product. A part of the sheet-like molded product was cut into 5 mm x 5 mm pieces using a cutter to obtain pellets.

[0184] Comparative Example 6 Example 9 was carried out in the same manner as in Example 1, except that 5 parts of the component (b1) were used instead of the component (B1), to obtain a sheet-shaped molding and pellets.

[0185] Comparative Example 7 Example 9 was carried out in the same manner as in Example 1, except that 5 parts of the component (b3) were used instead of the component (B1), to obtain a sheet-shaped molding and pellets.

[0186] Comparative Example 8 In Example 9, except that 5 parts of hydrogenated rosin ester (manufactured by Arakawa Chemical Industries, Ltd., product name "KE-311", softening point 96°C, color tone 20 Hazen) (hereinafter referred to as "component (b4)") was used instead of the component (B1), preparation was performed in the same manner as in Example 9 to obtain a sheet-shaped molding and pellets.

[0187] (Smoke generation evaluation) The pellets of Examples 9 to 14 and Comparative Examples 5 to 8 were injection molded at 290°C using a Handtruder M-1 (a tabletop manual injection molding machine / pelletizer manufactured by Toyo Seiki Seisakusho Co., Ltd.), and smoke generation during molding was visually evaluated and rated according to the following criteria. The results are shown in Table 2. ○: Almost no smoke. △: A small amount of smoke is produced. ×: A lot of smoke is emitted.

[0188] (Evaluation of dielectric tangent) Using a network analyzer (Keysight Technologies, device name "P5003A") and a split post dielectric resonator (QWED) with a measurement frequency of 10.124 GHz, the resonant frequency and peak Q value of the resonator alone with nothing inserted were measured. Next, the sheet-shaped molded products of Examples 9 to 14 and Comparative Examples 5 to 8 were inserted into the resonators, and then the resonant frequency and the Q value were measured when the sheet-shaped molded products were inserted. The dielectric loss tangent (Df) of the sheet-shaped molded products of Examples 9 to 14 and Comparative Examples 5 to 8 was calculated from the difference in the Q value and the difference in the resonant frequency between the resonator alone and when the sheet-shaped molded product was inserted.

[0189] The rate of increase in the dielectric loss tangent (Df) of the sheet-form moldings of Examples 9 to 14 and Comparative Examples 6 to 8 relative to the dielectric loss tangent (Df) of Comparative Example 5 (blank) was evaluated according to the following criteria. The results are shown in Table 2. The smaller the rate of increase in the dielectric loss tangent (Df), the more excellent the low dielectric properties. ○: The increase in dielectric tangent compared to the blank is less than 10% △: The increase in dielectric tangent compared to blank is 10% to less than 40% ×: The increase in dielectric tangent compared to the blank is 40% or more.

[0190] (MFR rating) In accordance with JIS K 7210, the MFR of each of the pellets of Examples 9 to 14 and Comparative Examples 5 to 8 was measured under conditions of a temperature of 300° C. and a load of 21.2 N (2.16 kg).

[0191] The increase rate of MFR of the pellets of Examples 9 to 14 and Comparative Examples 6 to 8 relative to the MFR of Comparative Example 5 (blank) was evaluated according to the following criteria. The results are shown in Table 2. The larger the increase rate of MFR, the more excellent the molding processability. 〇: MFR increase rate is 10% or more compared to blank △: The increase in MFR compared to blank is 3% to less than 10% ×: The increase in MFR compared to blank is less than 3%

[0192] [Table 2]

[0193] The blend amounts in Table 2 are given in parts by mass.

[0194] [Preparation of resin composition] Example 15 100 parts of glass fiber reinforced polyphenylene sulfide resin (manufactured by Toray Industries, Inc., product name "TORELINA A504X90", polyphenylene sulfide resin 60 mass%, glass fiber 40 mass%) (hereinafter, polyphenylene sulfide resin is the (A4) component, and glass fiber is the (C1) component) and 5 parts of the (B1) component were put into a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 310 ° C. Thereafter, the kneaded product (resin composition) obtained was taken out of the kneading device, hot pressed at 320 ° C., and molded into a sheet with a thickness of 1.0 mm to obtain a sheet-shaped molded product. In addition, a part of the sheet-shaped molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0195] Example 16 A sheet-like molding and pellets were obtained in the same manner as in Example 15, except that 5 parts of the component (B2) were used instead of the component (B1).

[0196] Example 17 A sheet-like molding and pellets were obtained by the same preparation as in Example 15, except that 5 parts of the component (B4) were used instead of the component (B1).

[0197] Example 18 A sheet-like molding and pellets were obtained by the same preparation as in Example 15, except that 5 parts of the component (B5) were used instead of the component (B1).

[0198] Example 19 A sheet-like molding and pellets were obtained in the same manner as in Example 15, except that 5 parts of the component (B6) were used instead of the component (B1).

[0199] Example 20 A sheet-like molding and pellets were obtained in the same manner as in Example 15, except that 5 parts of the component (B7) were used instead of the component (B1).

[0200] Comparative Example 9 100 parts of glass fiber reinforced polyphenylene ether resin (manufactured by Toray Industries, Inc., product name "TORELINA A504X90", 60% by mass of (A4) component, 40% by mass of (C1) component) was put into a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 320°C. Thereafter, the kneaded product obtained was removed from the kneading device, hot pressed at 320°C, and molded into a sheet having a thickness of 1.0 mm to obtain a sheet-like molded product. In addition, a part of the sheet-like molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0201] Comparative Example 10 A sheet-like molding and pellets were obtained in the same manner as in Example 15, except that 5 parts of the component (b1) were used instead of the component (B1).

[0202] (Smoke generation evaluation) The pellets of Examples 15 to 20 and Comparative Examples 9 to 10 were injection molded at 350°C using a Handtruder M-1 (a tabletop manual injection molding machine / pelletizer manufactured by Toyo Seiki Seisakusho Co., Ltd.), and smoke generation during molding was visually evaluated and rated according to the following criteria. The results are shown in Table 3. ○: Almost no smoke. △: A small amount of smoke is produced. ×: A lot of smoke is emitted.

[0203] (Evaluation of dielectric tangent) Using a network analyzer (Keysight Technologies, device name "P5003A") and a split post dielectric resonator (QWED) with a measurement frequency of 10.124 GHz, the resonant frequency and peak Q value of the resonator alone with nothing inserted were measured. Next, the sheet-shaped molded products of Examples 15 to 20 and Comparative Examples 9 to 10 were inserted into the resonators, and then the resonant frequency and the Q value were measured when the sheet-shaped molded products were inserted. The dielectric loss tangent (Df) of the sheet-shaped molded products of Examples 15 to 20 and Comparative Examples 9 to 10 was calculated from the difference in the Q value and the difference in the resonant frequency when the sheet-shaped molded product was inserted and the resonator alone.

[0204] The rate of increase in the dielectric loss tangent (Df) of the sheet-form moldings of Examples 15 to 20 and Comparative Example 10 relative to the dielectric loss tangent (Df) of Comparative Example 9 (blank) was evaluated according to the following criteria. The results are shown in Table 3. The smaller the rate of increase in the dielectric loss tangent (Df), the more excellent the low dielectric properties. ○: The increase in dielectric tangent compared to the blank is less than 10% △: The increase in dielectric tangent compared to blank is 10% to 30%. ×: The increase in dielectric tangent compared to the blank is 30% or more.

[0205] (Evaluation of Melt Viscosity) For the pellets of Examples 15 to 20 and Comparative Examples 9 to 10, the apparent melt viscosity at a temperature of 310°C and a shear rate of 2432 (1 / sec) was measured in accordance with JIS K7199 using a commercially available capillary rheometer (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Capillograph 1C").

[0206] The melt viscosity reduction rates of the pellets of Examples 15 to 20 and Comparative Example 10 relative to the melt viscosity of Comparative Example 9 (blank) were evaluated according to the following criteria. The results are shown in Table 3. The greater the melt viscosity reduction rate, the more excellent the molding processability. ○: The decrease in melt viscosity compared to the blank is 10% or more. △: The decrease in melt viscosity compared to the blank is 3% or more but less than 10%. ×: The decrease in melt viscosity compared to the blank is less than 3%.

[0207] [Table 3]

[0208] The blend amounts in Table 3 are given in parts by mass.

[0209] [Preparation of resin composition] Example 21 A glass fiber reinforced polybutylene terephthalate resin (manufactured by Toray Industries, Inc., product name "Trecon 1101G-30", polybutylene terephthalate resin 70% by mass, glass fiber 30% by mass) (hereinafter, polybutylene terephthalate resin is the (A5) component and glass fiber is the (C1) component) was added to a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") in an amount of 100 parts and 5 parts of the (B1) component, and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 245 ° C. Thereafter, the kneaded product (resin composition) obtained was taken out of the kneading device, hot pressed at 320 ° C., and molded into a sheet having a thickness of 1.0 mm to obtain a sheet-shaped molded product. In addition, a part of the sheet-shaped molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0210] Example 22 A sheet-like molding and pellets were obtained in the same manner as in Example 21, except that 5 parts of the component (B4) were used instead of the component (B1).

[0211] Example 23 A sheet-like molding and pellets were obtained in the same manner as in Example 21, except that 5 parts of the component (B7) were used instead of the component (B1).

[0212] Comparative Example 11 100 parts of glass fiber reinforced polybutylene terephthalate resin (manufactured by Toray Industries, Inc., product name "Trecon 1101G-30", 70% by mass of (A5) component, 30% by mass of (C1) component) was put into a roller mixer type kneading device (manufactured by Toyo Seiki Seisakusho Co., Ltd., device name "Labo Plastomill Model 10C100") and kneaded for 10 minutes at a roller rotation speed of 40 rpm and a temperature of 245°C. Thereafter, the kneaded product (resin composition) obtained was taken out of the kneading device, hot pressed at 320°C, and molded into a sheet having a thickness of 1.0 mm to obtain a sheet-like molded product. In addition, a part of the sheet-like molded product was cut into 5 mm x 5 mm with a cutter to obtain pellets.

[0213] Comparative Example 12 A sheet-like molding and pellets were obtained in the same manner as in Example 21, except that 5 parts of the component (b1) were used instead of the component (B1).

[0214] (Smoke generation evaluation) The pellets of Examples 21 to 23 and Comparative Examples 11 to 12 were injection molded at 350°C using a Handtruder M-1 (a tabletop manual injection molding machine / pelletizer manufactured by Toyo Seiki Seisakusho Co., Ltd.), and smoke generation during molding was visually evaluated and rated according to the following criteria. The results are shown in Table 4. ○: Almost no smoke. △: A small amount of smoke is produced. ×: A lot of smoke is emitted.

[0215] (Evaluation of dielectric tangent) Using a network analyzer (Keysight Technologies, device name "P5003A") and a split post dielectric resonator (QWED) with a measurement frequency of 10.124 GHz, the resonant frequency and peak Q value of the resonator alone with nothing inserted were measured. Next, the sheet-shaped molded products of Examples 21 to 23 and Comparative Examples 11 to 12 were inserted into the resonators, and then the resonant frequency and the Q value were measured when the sheet-shaped molded products were inserted. The dielectric loss tangent (Df) of the sheet-shaped molded products of Examples 21 to 23 and Comparative Examples 11 to 12 was calculated from the difference in the Q value and the difference in the resonant frequency between the resonator alone and when the sheet-shaped molded product was inserted.

[0216] The rate of increase in the dielectric loss tangent (Df) of the sheet-form moldings of Examples 21 to 23 and Comparative Example 12 relative to the dielectric loss tangent (Df) of Comparative Example 11 (blank) was evaluated according to the following criteria. The results are shown in Table 4. The smaller the rate of increase in the dielectric loss tangent (Df), the more excellent the low dielectric properties. ○: The increase in dielectric tangent compared to the blank is less than 10% △: The increase in dielectric tangent compared to blank is 10% to less than 40% ×: The increase in dielectric tangent compared to the blank is 40% or more.

[0217] (MFR rating) In accordance with JIS K 7210, the MFR of each of the pellets of Examples 21 to 23 and Comparative Examples 11 to 12 was measured under conditions of a temperature of 300° C. and a load of 21.2 N (2.16 kg).

[0218] The rate of increase in MFR of the pellets of Examples 21 to 23 and Comparative Example 12 relative to the MFR of Comparative Example 11 (blank) was evaluated according to the following criteria. The results are shown in Table 4. The greater the rate of increase in MFR, the more excellent the molding processability. 〇: MFR increase rate is 10% or more compared to blank △: The increase in MFR compared to blank is 3% to less than 10% ×: The increase in MFR compared to blank is less than 3%

[0219] [Table 4]

[0220] The blend amounts in Table 4 are given in parts by mass.

Claims

1. The composition comprises at least one resin (A) selected from the group consisting of a liquid crystal polymer, a polyphenylene sulfide resin, and a polybutylene terephthalate resin, and a petroleum resin (B); The 5% weight loss temperature of the petroleum resin (B) is 270° C. or higher, The petroleum resin (B) has a mixed methylcyclohexaneaniline cloud point (MMAP) of 10 to 95°C.

2. A composition comprising a polyphenylene ether resin and a petroleum resin (B), The 5% weight loss temperature of the petroleum resin (B) is 270° C. or higher, The petroleum resin (B) has a mixed methylcyclohexaneaniline cloud point (MMAP) of 80 to 95°C.

3. The resin composition according to claim 1 , wherein the liquid crystal polymer is a liquid crystal polyester.

4. The resin composition according to claim 1 or 2, wherein the softening point of the (B) component is 120 to 190°C.

5. The resin composition according to claim 1 or 2, wherein the content of the component (B) is 0.1 to 10 parts by mass per 100 parts by mass of the component (A).

6. A molded article obtained from the resin composition according to claim 1 or 2.

7. The 5% weight loss temperature is 270° C. or higher; A flow improver for low dielectric resins, comprising a petroleum resin (B) having a mixed methylcyclohexaneaniline cloud point (MMAP) of 10 to 95° C.; The low dielectric resin is at least one resin selected from the group consisting of a liquid crystal polymer, a polyphenylene sulfide resin, and a polybutylene terephthalate resin. A flow improver for low dielectric resins.

8. The 5% weight loss temperature is 270°C or higher, A flow improver for low dielectric resins, comprising a petroleum resin (B) having a mixed methylcyclohexaneaniline cloud point (MMAP) of 80 to 95°C; The low dielectric resin is a polyphenylene ether resin. A flow improver for low dielectric resins.

9. 9. The flow improver for low dielectric resins according to claim 7 or 8, wherein the softening point of component (B) is 120 to 190° C.

Citation Information

Patent Citations

  • Polyarylene sulfide resin composition

    JP1996157717A

  • Polyphenylene ether resin composition

    JP1997059508A

  • Liquid crystalline aromatic polyester for insulating material and resin composition thereof

    JP2004250620A

  • Polycarbonate resin composition and retardation film

    JP2006143832A

  • Polybutylene terephthalate resin composition

    JP2013043942A